Hashtagging for Health Promotion: Constructing Meaning as an #AntibioticGuardian (Altre Modernità, 2018)
This paper aims at investigating how the hashtag constructs meanings in public health campaigns in Twitter. These may have peculiar features due to the simultaneous influence of the character-constrained mode of Twitter, and of the conventional set of communication activities adopted to ensure their effectiveness. The research is based on a corpus of sample tweets (N=2,438) taken from #AntibioticGuardian, a campaign led by Public Health England to reduce Antimicrobial Resistance (AMR). The lexicogrammatical realisations, evaluative language and predominant discourse functions are analysed to seek the meanings that the hashtag can construct in each of the four communication activities, namely increasing awareness and knowledge, providing cues for action, demonstrating simple skills, and changing and/or reinforcing attitudes and behaviours. The method of positive discourse analysis (PDA) used offers the advantage of highlighting how the positive change advocated takes place linguistically; micro and macro data findings reveal a significant user-generated content (UGC) pattern reflecting new ways of making meaning, which moves far beyond the more traditional tagging practices.